Vertebrate Fossils in Fatha, Injana and Mukdadiya Formations in Iraq - Abbas Al- Zubaidi, Aqeel; Khan Jan, Saadi (Iraqi Journal of Science, 2023)
This study showed that the rock bed units of Fatha (M. Miocene) includes mold of fish fossils imprint on marly limestone; Injana (L. Miocene) includes large femur bone of Mastodont and large number of bone remains; and review study of Mukdadiya Formations (Pliocene) showed more than 21 mamalian species such as: Mastodont, Hipparion, Gazzella, Felidae, Bovidae, Antilopini, Caprinae, Crocodilia, and others. Those vertebrate fossils bones were deposited and preserved within rock bed units of fluvial and evaporite marine environments. Paleoenvironment of fluvial ecosystem made up of food chain, which were includes producer, herbivores as a primary consumer as Mastodon, Hipparion and Gazelle, carnivores as a secondary consumer as felidea and crocodilia and omnivores as aves; and restricted marine ecosystem were includes producer, minute foraminifera and primary or secondary consumer as fish.